Grupo sanguíneo O perigoso: a realidade da Fundação Hemominas, Hemocentro de Belo Horizonte, Minas Gerais - Mariana Martins Godin (2015)
Blood transfusion is an effective therapy, although it is associated with risks. The term "Dangerous Universal Donor" refers to the potential of receptors erythrocytes agglutination due the serum of group "O" donors. Obtaining platelet apheresis has become routine in blood banks. Knowing that the platelet concentrate carries a significant volume of plasma, there was a concern with the titer of anti-A and anti-B agglutinins. Therefore, the prior titration of agglutinins has been encouraged for the prevention of transfusion reactions. The aim of this study was to estimate the "O" dangerous donor frequency from the Blood Center in Belo Horizonte/MG, through the determination of the anti-A and anti-B agglutinins titers in "O" blood group donors. Four hundred "O" blood group samples were analyzed by tube titration technique and the titers of anti-A and anti-B agglutinins IgM and IgG classes were obtained. Dangerous donors were those who had titers of anti-A and/or anti-B IgM128 and/or titer of anti-A and/or anti-B IgG256. Donors were characterized by gender, age and ethnicity. The agglutinins were characterized as specificity (anti-A and anti-B) and antibody class (IgG and IgM). The statistical analysis was done by chi-square test and Fisher's exact test. The odds ratio (OR) was determined for the variables that were significantly correlated. Of the 400 samples evaluated, 209 were from men (52.3%) and 191 from women (47.7%). Concerning to the age, 169 donors were1829 years old (42.2%); 116, 29-39 years old (29.0%); 69, 39-49 years old (17.3%); 36, 49-59 years (9.0%), and 10, 59-69 (2.5%). Regarding to ethnicity, 208 classified themselves as brown (52%); 136 as caucasian (34%), 54 as black (13.5%) and 2 (0.5%) as asiatic. The results revealed that 30.5% of the "O" blood group donors are "O" dangerous (56.6%, female and 43.4%, male). Among donors classified as "O" dangerous, the frequency of women was higher than men (P=0.019; OR=1.66, RC=1,66; CI95%=1,08-2,56). The frequency among young donors (18 to 29 years old) was greater than in adults (49-59 years old) (P=0.015; OR=3.05, CI95%=1,22-7,69). The analysis of 1600 titrations showed that in 88 and 84 of them, the anti-A and antiB agglutinins characterized donors as hazardous, respectively. The analysis of 1600 titrations analyzes revealed that in 76 and 68 of them, IgM and IgG antibody classes characterized donors as hazardous, respectively. For ethnicity, agglutinin specificity and antibody class there were no significant correlations between groups. The great merit of this study was to arouse the interest of Fundação Hemominas for the issue of "Dangerous Universal Donor". This determined the beginning of the standardization of automated titration in the Central de Imuno-Hematologia, an important step toward making transfusion a safer therapy for patients who benefit from the "O" blood group products.